Body size influences differently the detectabilities of colour morphs of cryptic prey. (4th June 2014) - Karpestam, Einat; Merilaita, Sami; Forsman, Anders
<x xml:space="preserve">Abstract</x> Body size and coloration may contribute to variation in performance and fitness among individuals; for example, by influencing vulnerability to predators. Yet, the combined effect of size and colour pattern on susceptibility to visual predators has received little attention, particularly in camouflaged prey. In the colour polymorphic pygmy grasshopper Tetrix subulata (Linnaeus, 1758), females are larger than males, although there is a size overlap between sexes. In the present study, we investigated how body size and colour morph influenced detection of these grasshoppers, and whether differences in protective value among morphs change with size. We conducted a computer‐based experiment and compared how human 'predators' detected images of large, intermediate or small grasshoppers belonging to black, grey or striped colour morphs when embedded in photographs of natural grasshopper habitats. We found that time to detection increased with decreasing size, that differences in time to detection of the black, grey and striped morphs depended differently on body size, and that no single morph provided superior or inferior protection in all three size classes. By comparing morph frequencies in samples of male and female grasshoppers from natural populations, we also examined whether the joint effects of size and colour morph on detection could explain evolutionary dynamics in the wild. Morph frequency differences between sexes were largely in accordance with expectations from the results of the detection experiment. The results of the present study demonstrate that body size and colour morph can interactively influence detection of camouflaged prey. This may contribute to the morph frequency differences between male and female pygmy grasshoppers in the wild. Such interactive effects may also influence the dynamics of colour polymorphisms, and contribute to the evolution of ontogenetic colour change and sexual dichromatism. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 113, 112–122.